Peningkatan Aktivitas Belajar Akidah Akhlak Melalui Model Pembelajaran IOC Materi Sifat Wajib Allah - Sulastri (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2024)
This research is motivated by teaching and learning activities which tend to be monotonous through the lecture method so that student learning activities are reduced. To overcome the problems mentioned above, it is necessary to prepare a teaching and learning process that uses appropriate learning models. The purpose of this research is to determine the increase in learning activities regarding moral beliefs regarding the obligatory nature of Allah through the IOC (Inside Outside Circle) learning models. This research is classroom action research carried out in three cycles. In cycles I, some students were still not used to the IOC model learning conditions. In cycles II and III, students and teachers began to understand the application of IOC learning model and showed satisfactory results. From the results of observations, students’ activity increased from 63% of learning activities (before using the IOC model) in cycle I, to 71% in cycle II (after using the IOC model), and 82% in cycle III. Meanwhile, the results of the daily tests showed an increase from an average of 61 in the first test (before using the IOC model) to an average of 73 in the second daily test and to an average of 81 in the third daily test (after using the IOC model). From the implementation of the first, second, and third cycles of classroom action research, it can be concluded that the IOC learning model can improve students learning activities and students learning outcomes in learning moral belief on the material of Allah’s obligatory nature.